خاتم النبیین ﷺکے دورمدنی میں اسلامی معاشرت کی بنیادیں: An Analytical Study of The Foundations of Islamic Society in The Madani Period of Muhammad (PBUH) Khatam-Ul-Nabieen - Suddah Karam; Nosheen Karam; Muhammad Irshad (Al Manhal Research Journal, 2025)
It is impossible to deny that before the arrival of the Mercy of the Universe, the Wise Mankind, and the Prophet of Mankind, the condition of humanity was in a terrible state. There was a period of ignorance and misguidance, oppression and violence reigned, and the exploitation and tyranny were on the rise. The market for looting was hot, so humanity as a whole was groaning. The mercy of God was excited and a bright sun shone from the peaks of Faran which Allah Almighty sent as a gift for all mankind. The era after the Messenger of Allah (PBUH) consisted of two stages, and the two eras brought the lesson of peace and security. After facing many hardships in Makkah, He was ordered to migrate by Allah Almighty. As soon as he arrived in Madinah, He (PBUH) created the foundations and values that pave and decorate the path of success for all humanity until the Day of Resurrection. Social solidarity and cooperation, the Covenant of Medina, mutual Counselling, friendships between refugees and helpers, good behaviour towards responsible people, construction of mosques and the foundations of the political system, these are the economic base and foundations .Who brought out the society and humanity immersed in ignorance and darkness from ignorance and put the antidote of Islam on its evils with the hands full of compassion, brought about the revolution with his good morals, the example of which is impossible in the history of the world. The same foundations are being mentioned in this Article.